Antimicrobial photodynamic therapy: an effective alternative approach to control fungal infections - Baltazar, Ludmila M.; Ray, Anjana; Santos, Daniel A.; Cisalpino, Patrícia S.; Friedman, Adam J.; Nosanchuk, Joshua D. (Frontiers in Microbiology, 2015)
Skin mycoses are caused mainly by dermatophytes, which are fungal species that primarily infect areas rich in keratin such as hair, nails and skin. Significantly, there are increasing rates of antimicrobial resistance among dermatophytes, especially for Trichophyton rubrum, the most frequent etiologic agent worldwide. Hence, investigators have been developing new therapeutic approaches, including photodynamic treatment. Photodynamic therapy utilizes a photosensitive substance activated by a light source of a specific wavelength. The photoactivation induces cascades of photochemicals and photobiological events that cause irreversible changes in the exposed cells. Although photodynamic approaches are well established experimentally for the treatment of certain cutaneous infections, there is limited information about its mechanism of action for specific pathogens as well as the risks to healthy tissues. In this work, we have conducted a comprehensive review of the current knowledge of photodynamic therapy as it specifically applies to fungal diseases. The data to date suggests that photodynamic treatment approaches hold great promise for combating certain fungal pathogens, particularly dermatophytes.